2020
DOI: 10.3389/fped.2020.00129
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Regulation of Macrophage Marker Expression Profiles in Kawasaki Disease

Abstract: Kawasaki disease (KD) is a common systemic vasculitides in children younger than 5 years of age. Activated macrophages are key drivers of vascular inflammation in KD. The aim of this study was to examine differences in M1 and M2 macrophage marker expression in patients with KD. Blood samples were obtained from 18 healthy controls and 18 patients with KD at 24 h prior and 21 days after to intravenous immunoglobulin therapy. GeneChip Human Transcriptome Array 2.0 and Illumina HumanMethylation450 BeadChip were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 45 publications
2
20
0
Order By: Relevance
“…The lungs' classically activated macrophages (M1) expressing proinflammatory cytokines and alternatively activated macrophages (M2) expressing Th2 cytokines both participate in the pathogenesis of asthma (59). One recent study suggested that M1 and M2 cells are distinct cell subtypes that play separate roles in the immunopathogenesis of KD and also showed M2 to be predominant (Figure 2) (60).…”
Section: Abnormal Type 2 Inflammation Imbalance T Helper Type 17/regmentioning
confidence: 99%
“…The lungs' classically activated macrophages (M1) expressing proinflammatory cytokines and alternatively activated macrophages (M2) expressing Th2 cytokines both participate in the pathogenesis of asthma (59). One recent study suggested that M1 and M2 cells are distinct cell subtypes that play separate roles in the immunopathogenesis of KD and also showed M2 to be predominant (Figure 2) (60).…”
Section: Abnormal Type 2 Inflammation Imbalance T Helper Type 17/regmentioning
confidence: 99%
“…We used two TLR4 RNA probes in the Danish twin study and both probes were significantly inversely correlated to TLR4 methylation. In a recent report by Guo et al, patients with Kawasaki disease had decreased methylation in leukocytes of cg05429895 (and two other TLR4 CpGs) and higher mRNA TLR4 levels [67], indicating that an increase in methylation at this particular site likely contributes to decreased RNA expression levels. Elevated TLR4 mRNA has been described before in blood cells from depressed patients [15,26,].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, transcriptomic profiling using GeneChip array in patients with acute phase of KD has showed elevated expression of TLR2 and IL2RA (M1 macrophage) in addition to markers associated with M2 macrophage (e.g., MS4A4A, MS4A6A, TLR1, TLR8, TLR5, CD36, CCR2, and ARG1). Authors have also noted hypomethylation of the promoter region of respective genes (17). IVIg treatment given to these patients has further enhanced the expression pattern of these genes by enriching the hypomethylation status.…”
Section: Methylation and Kdmentioning
confidence: 95%
“…Epigenetics is widely explored in most of complex heterogenic diseases like KD where contribution of both genetic and environmental factors is equally shared (14)(15)(16)(17). Genetic predisposition of complex disease phenotypes has been associated with substantial contribution of dysregulated epigenetic factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation